(untitled) (Research, Society and Development, 2021)
Innovation has been treated as a relevant issue in organizations, where increasingly obtaining competitive advantages has become a way to remain in the market. One of the pillars that allow this process is the organizational culture where participation and interaction between people and departments favor this process. In this sense, the study seeks to map and analyze how the organizational culture in a small company in the metallurgical industry can influence the innovation process. The methodology used was descriptive from a case study, through a qualitative and quantitative approach, as data collection instruments, a questionnaire was applied to all employees of the company and a semi-structured interview was carried out with its directors. The result points out as positive the guidelines taken by the organization.